Computational screening of natural inhibitors against Plasmodium falciparum kinases: Toward novel antimalarial therapies - Muharib Alruwaili; Sonia Younas; Abozer Y. Elderdery; Intisar Alruwaili; Jeremy Millis; Muhammad Umer Khan; Hasan Ejaz (PLoS ONE, 2026)
An important worldwide problem is the resistance of Plasmodium falciparum to practically all antimalarial medications. Therefore, new treatment approaches are urgently needed. The development of antimalarial medications frequently involves two important therapeutic targets: casein kinase 2 (CK2) and cGMP-dependent protein kinase (PKG). To identify naturally occurring chemicals that could be used as antimalarial medications to combat multidrug-resistant P. falciparum , we used a multi-targeted in silico strategy in this study. The top 20 compounds, including the reference drug RY-1–65, were selected after pharmacophore-based virtual screening of naturally produced compounds. These compounds were subsequently docked onto both target proteins using Maestro (Schrödinger 2020−3). The best-scoring compounds against PKG and CK2 were Ligand-9 (−7.490 kcal/mol) and Ligand-13 (−11.468 kcal/mol), respectively. These lead compounds may be useful as therapeutic targets based on an assessment of their pharmacological, toxicological, and bioactivity characteristics. Furthermore, Ligand-13’s strong reactivity and stability were demonstrated by density functional theory analysis, and these findings were confirmed by molecular dynamics simulations and binding free energy MMGBSA calculations. These results imply that Ligand-13 may be a promising antimalarial medication.